Diagnóstico das condições para implantação da Modelagem da Informação da Construção (BIM) em municípios de pequeno porte - Alves, Thiago Rodrigo de Oliveira (Universidade Federal de São Carlos, 2021)
Building Information Modeling (BIM) methodology currently represents one of the main options for modernizing and restructuring design and construction practices for the Architecture, Engineering, Construction and Operations (AECO) sector. To provide more significant savings, efficiency, and transparency to its projects, the Federal Government prepared the National BIM Dissemination Strategy, also known as the BIM-BR Strategy. The first phase aims to apply BIM methodology to develop public projects for architecture and engineering. This study aims to verify the conditions of receptivity and existing infrastructure for implementing BIM by the management of small municipalities, that is, those with a population of fewer than 20 thousand inhabitants. A pilot study of a descriptive and exploratory case study was first carried out to seek validation for the elaborated questionnaire. The survey was carried out with nine small municipalities located in the northwest region of the State of São Paulo, verifying the conditions of receptivity, infrastructure and analyzing professionals' perceptions regarding the possible obstacles to BIM realization. Despite the possible benefits of implementing the BIM methodology, it was lying that several barriers can impede the dissemination process. The professionals' experience, financial factors, staff availability, equipment, and program requirements were some perceived difficulties in introducing the new tools. Finally, it was verified that the assistance of other government instances to carry out investments in the modernization of equipment and systems of small city halls would be crucial for the future dissemination of BIM for this group. Simple initiatives, such as the development of normative instruments, training and qualifications, and the implementation of communication management systems between sectors, can also help to improve BIM's receptivity by small-sized city halls.
Diagnosis of the conditions for implementing Construction Information Modeling (BIM) in small municipalities
Keywords: Construção civil; Modelagem da Informação da Construção; Projetos públicos; Municípios de pequeno porte; BIM-BR; Construction industry; Building Information Modeling; Public projects; Small municipalities; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL